87.5k views
3 votes
Divide -2x^3-5x^2+4x+2 by x+2

Answers
A. -2x^2-x+6
B. -2x^2-x+6, R 14
C. -2x^2-x+6, R(-10)
D. -2x^2-9x+22,R(-42)

PLEASE HELP!!

1 Answer

5 votes

Answer:

The correct option is C.
-2x^2-x+6, R(-10)

Explanation:

Given:

Dividend = -2x^3-5x^2+4x+2

Divider =(x+2)

Solution:

Now by using the division method , we will find out the quotient and remainder of the given equation

And the equation will become


-2x^3-5x^2+4x+2=(x+2)(-2x^2-x+6)-10

So , We will get the quotient =
-2x^2-x+6

And Remainder = -10

Hence the Correct option which perfectly satisfy the given equation is C.

User Gtonic
by
5.1k points